A rare case of right heart failure with the necessity for veno‐arterial extracorporeal membrane oxygenation following pulmonary vein stenosis after radiofrequency ablation for atrial fibrillation. (21st February 2023) - Kopp, Sabrina; Tilch, Marie‐Kristin; Sagoschen, Ingo; Kaes, Joachim; Kuniss, Malte; Neumann, Thomas; Yang, Yang; Schnitzler, Katharina; Schmidt, Kai‐Helge; Rostock, Thomas; Münzel, Thomas; Konstantinides, Stavros; et al.
Abstract: Pulmonary vein stenosis (PVS) after radiofrequency energy‐mediated percutaneous pulmonary vein isolation as a treatment option for atrial fibrillation is a serious complication and the prevalence in historical reports varies between 0% and 42%. Symptoms of PVS are nonspecific and can include general symptoms such as dyspnea, cough, recurrent pneumonia, and chest pain. Pathophysiologically it increases the postcapillary pressure in the pulmonary circuit and may result in pulmonary hypertension (PH). Misdiagnosis and delayed treatment are common. We here report a case of a 59‐year‐old female with a history of pulmonary vein ablation followed by progressive dyspnea (New York Heart Association IV), right heart failure, CPR, and the need for extracorporeal membrane oxygenation (ECMO). Further treatment strategy includes pulmonary vein dilatation and stenting of both the left superior pulmonary vein and left inferior pulmonary vein, as well as balloon dilatation of RIPV under temporary ECMO support. Symptomatic, severe PVS is a rare complication after catheter ablation of atrial fibrillation. PVS can result in life‐threatening complications such as PH with acute right heart failure. Early diagnosis is crucial but challenging. Mechanical cardiopulmonary support by veno‐arterial ECMO for bridging to angioplasty could be a lifesaving option.